The taxonomy of spider crabs of the genera Eurynome, Choniognathus, Seiitaiodes and Kasagia (Crustacea: Brachyura: Majidae) from southwest Indian Ocean - de Forges, Bertrand Richer; Lee, Bee Yan; Ng, Peter K. L. (Zootaxa, 2021)
The taxonomy of majid spider crabs collected from recent southwest Indian Ocean cruises belonging to Eurynome Leach, 1814, and allied genera is treated. Eurynome longimana Stimpson, 1857, long synonymised with the European E. aspera (Pennant, 1777), is here recognised as a distinct species. Stimpson’s (1857) species can be distinguished by the armature of granules on the third maxilliped, proportions and armature of the ambulatory merus, relatively shorter ambulatory dactylus, structure of the male sternopleonal cavity and relative proportions of the male first gonopod. The composition of Choniognathus Rathbun, 1932, is discussed and the type species, C. koreensis Rathbun, 1932, is figured. One species, C. verhoeffi (Balss, 1929), is not considered to be a member of Choniognathus and its taxonomy is discussed. A new spinose species, C. spinosus, is also described. Seiitaoides Griffin & Tranter, 1986, is revised, and two new species, S. mirabilis and S. kabuto, are described and compared with S. orientalis (Sakai, 1961) and S. stimpsoni (Miers, 1884). The poorly known Eurynome elegans Stebbing, 1921 is rediscovered, its taxonomy clarified and the species is shown to belong to Kasagia Richer de Forges & Ng, 2007. A second species of Kasagia, K. sudhakari Padate, Manjebrayakath & Ng, 2019, recently described from the Arabian Sea is recorded from southwest Indian Ocean.